2015
DOI: 10.1016/j.ijcard.2015.05.106
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of where reperfusion ventricular arrhythmia “bursts” fit into optimal reperfusion in STEMI

Abstract: PREPARE: ISRCTN71104460 http://www.controlled-trials.com/ISRCTN71104460.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…VAs upon reperfusion have been recognized since the advent of recanalization techniques [ 152 ]; however their pathophysiological and prognostic significance is still controversial [ 153 ]. Several arrhythmogenic mechanisms have been proposed to be involved in IRI-induced arrhythmias [ 154 , 155 ].…”
Section: Ischemia/reperfusion Injury and Medicolegal Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…VAs upon reperfusion have been recognized since the advent of recanalization techniques [ 152 ]; however their pathophysiological and prognostic significance is still controversial [ 153 ]. Several arrhythmogenic mechanisms have been proposed to be involved in IRI-induced arrhythmias [ 154 , 155 ].…”
Section: Ischemia/reperfusion Injury and Medicolegal Issuesmentioning
confidence: 99%
“…Several arrhythmogenic mechanisms have been proposed to be involved in IRI-induced arrhythmias [ 154 , 155 ]. Some of VAs that occur almost directly at the moment of reperfusion (namely, ventricular premature beats and accelerated idioventricular rhythms) are usually harmless and well tolerated [ 152 ]; however it has been reported that ventricular tachycardia and ventricular fibrillation occurring immediately after reperfusion remain the most important causes of sudden death following restoration of blood flow [ 156 , 157 ].…”
Section: Ischemia/reperfusion Injury and Medicolegal Issuesmentioning
confidence: 99%
“…This connection is supported by previous findings by our group. [3][4][5][6][7][8][9] We found, in several independent cohorts, the presence of a 'burst' of ventricular reperfusion arrhythmias (VA burst) to be related to clinically significant larger infarct size. This increase remained while correcting for other known factors of increased infarct size.…”
Section: Correlation Between Fatal Reperfusion Injury and Reperfusionmentioning
confidence: 95%
“…reopening of the infarct vessel, more recent studies have shown that reperfusion without arrhythmias resulted in smaller infarcts in spite of equal initial areas at risk. [3][4][5][6][7][8]…”
Section: Reperfusion Arrhythmiasmentioning
confidence: 99%
“…2 A statistical objectification of these reperfusion VAs, in which they were quantified against a subject-specific background VA rate as a new 'burst' of VA following angiographic recanalisation of the infarct artery, has confirmed these findings. [3][4][5][6][7] The involvement of microvascular obstruction (MVO) in the pathogenesis of VA burst is unknown. MVO is a known marker of additional extensive injury and larger IS, worse left ventricle ejection fraction (LVEF), left ventricle (LV) remodelling and a higher incidence of cardiovascular complications.…”
Section: Introductionmentioning
confidence: 99%